Perguruan Silat dan Perubahan Sosial : Upaya Pagar Nusa dalam Melestarikan Tradisi Islam di Kecamatan Nogosari: Silat Schools and Social Change: Pagar Nusa's Efforts to Preserve Islamic Traditions in Nogosari District - Muhammad Ilham; Viki Khoirul Fuady (Al-Absah: Journal of Civilization, Language, Literature, and History, 2025)
This study aims to explore the role of Nahdlatul Ulama's martial arts organization, Pagar Nusa, in Nogosari District in preserving Islamic civilization amid social change. Using a descriptive qualitative research method, this study was conducted in Nogosari, Boyolali, with the research object being the Pagar Nusa Nogosari District trainers. Data collection techniques used were interviews, observations, and documentation. Data analysis included data condensation, data presentation, and verification. This study investigates the organization's historical background, educational system, religious activities, and social impact. The findings show that Pagar Nusa serves not only as a martial arts institution but also as a platform for building Islamic character and spiritual development. Practices such as dhikr Tahlil, Rotiban, and Mujahadahan are used to instill Islamic values in members' daily lives. Moreover, the structured training levels and integration of Islamic principles position Pagar Nusa as a strategic force to face modern challenges and maintain social harmony. This study also highlights the uniqueness of Pagar Nusa Nogosari, including the 12 sikap pasang. The organization's activities have a positive impact on the community, providing security and promoting spiritual growth. This study concludes that Pagar Nusa is an essential part of NU's efforts to promote Islamic values and community development.